Novel hydroxide precursors to prepare NaNbO3 and KNbO3 - Muthurajan, H.; Kumar, H. H.; Samuel, V.; Gupta, U. N.; Ravi, V. (Ceramics International, 2008)
Firstly, fresh niobium, hydroxide was precipitated from NbF5 solution using an aqueous ammonium hydroxide under basic conditions. Then a simple procedure of mixing potassium (or sodium) and niobium hydroxides together and heating at a low temperature (<400 degrees C) produced KNbO3 (KN) or NaNbO3 (NN) powders. This is the lowest temperature so far reported for the formation of these phases. The phase content and lattice parameters are determined by X-ray diffraction (XRD). The average particle size and morphology were studied by scanning electron microscopy (SEM). (c) 2007 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: chemical preparation; niobates; Perovskites; powders; X-ray methods